PTU-161 Chronic norovirus infection as a cause of common variable immunodeficiency-associated enteropathy. (28th May 2012) - Woodward, J; Ng, A; Aravinthan, A; Bandoh, B; Liu, H; Davies, S; Stevenson, P; Curran, M; Kumararatne, D
Abstract : Introduction: A severe enteropathy with villous atrophy occurs in up to 15% of patients with common variable immunodeficiency (CVID). This study set out to determine the role of Norovirus infection in this condition. Methods: Stool and archived small intestinal biopsies from patients with CIVD enteropathy were analysed by PCR for the presence of Norovirus RNA. PCR products were sequenced to determine the relationship of viral isolates. Stool samples from ten asymptomatic patients with CVID served as controls. Results: All seven patients in our CVID cohort with enteropathy and villous atrophy showed persistent faecal norovirus excretion. No other entero- or parechovirus infection was apparent in any patient. Analysis of archived duodenal biopsies demonstrated the presence of the same viral strain (genotype II.4) in individuals over periods of up to 8 years. The presence of norovirus was strongly associated with villous atrophy in all our cases. Asymptomatic CVID patients showed no evidence of norovirus excretion. Conclusion: Chronic norovirus infection occurs in patients with common variable immunodeficiency-associated enteropathy and is strongly associated with villous atrophy and symptomatic malabsorption in all patients with CVID in this cohort. Chronic Norovirus is implicated as a major cause of CVID enteropathy. Competing interests: None declared.